A-Site Deficient La2-XNiO4+δ Infiltrated LSCF Cathode with Improved Performance and Stability. (30th May 2017) - Zhang, Xinxin; Li, Wenyuan; Guan, Bo; Liu, Xingbo
Abstract : In this study, A-site deficient lanthanum nickelate (La2-x NiO4±δ ) are explored as infiltrants. La2-x NiO4±δ (x=0-0.2) samples are synthesized and characterized first. La2-x NiO4±δ with high deficient exhibits enhanced electrical conductivity. Through the electrochemical impedance spectroscopy on the symmetrical cells, it is found that A-site deficiency lead to an increase in the polarization resistance. The surface charge transfer process gradually dominates the polarization resistance as lanthanum deficiency increases. In the infiltrated LSCF cathode, it is observed that about one order of magnitude improvement in the polarization resistance has been achieved after La2-x NiO4±δ infiltration, with La2 NiO4±δ -infiltration being the best. In a short-term measurement of 16 h under cathodic polarization of -0.2V, the degradation rate of La2-x NiO4+δ (x=0-0.2) coated LSCF reduces with the increasing A-site deficiency. The enhanced stability of La2-x NiO4+δ (x=0-0.2) coated LSCF demonstrates that A-site deficient La2-x NiO4+δ are promising infiltration materials for LSCF cathode for the improvement of the electrode stability.